Palladium-catalyzed arylation of 1, 4-naphthoquinones with aryl iodides and its synthetic application to the benzo[b]phenanthridine skeleton. Issue 44 (29th October 2020) - Akagi, Yusuke; Komatsu, Toshiya
Graphical abstract: Highlights: Aryl-1, 4-naphthoquinones are attractive synthetic targets. A Pd-catalyzed arylation of 1, 4-naphthoquinones with aryl iodides was reported. The benzo[ b ]phenanthridine skeleton was constructed. Abstract: We report a Pd-catalyzed arylation of 1, 4-naphthoquinones with aryl iodides. This reaction shows excellent functional group tolerance and high regioselectivity when using nonsymmetric 1, 4-naphthoquinone. Furthermore, the resulting 2-aryl-1, 4-naphthoquinone could be successfully converted into benzo[ b ]phenanthridine-7, 12-dione through treatment with aqueous ammonia, followed by oxidative cyclization using MnO2 .